On the Effect of Stellar Wind Braking onto the Central Object - Sauty, Christophe; Globus, Noemie; Meliani, Zakaria; Tsinganos, Kanaris; Vlahakis, Nektarios; Trussoni, Edo (Protostellar Jets in Context, 2009)
Stellar winds seem to be very efficient at removing angular momentum from stars. By means of analytical axisymmetric solutions of the ideal MHD equations for steady outflows, we show via a specific example how collimated stellar winds can brake Weak T Tauri stars in a reasonable time. This result can be generalized to Classical T Tauri stars provided that part of the accreted angular momentum is removed by the inner disk wind. We also extend briefly to Kerr metrics the self similar MHD solutions for relativistic flows and conjecture that relativistic outflows may efficiently slow down spinning black holes at the center of Active Galactic Nuclei or microquasars.
Keywords: physics